2020
DOI: 10.1155/2020/1508764
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Obesity on Outcome in Preclinical Animal Models of Infection and Sepsis: A Systematic Review and Meta-Analysis

Abstract: Background. Clinical studies suggest obesity paradoxically increases survival during bacterial infection and sepsis but decreases it with influenza, but these studies are observational. By contrast, animal studies of obesity in infection can prospectively compare obese versus nonobese controls. We performed a systematic review and meta-analysis of animal investigations to further examine obesity’s survival effect in infection and sepsis. Methods. Databases were searched for studies comparing survival in obese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…Despite obesity being protective in terms of survival, HFD-fed mice experienced greater incidence of kidney injury, as evidenced by increased expression of renal NGAL and elevated plasma creatinine. These results are in line with murine and clinical data (9,44). IL-17A, which is the only inflammatory cytokine having significantly higher levels in the septic HFD-fed mice in our study, has been shown to contribute to kidney injury in CLP-induced sepsis, as knockout of IL-17A improved functional and morphological measures of AKI, and exogenous administration of IL-17A aggravated AKI (45).…”
Section: Discussionsupporting
confidence: 90%
“…Despite obesity being protective in terms of survival, HFD-fed mice experienced greater incidence of kidney injury, as evidenced by increased expression of renal NGAL and elevated plasma creatinine. These results are in line with murine and clinical data (9,44). IL-17A, which is the only inflammatory cytokine having significantly higher levels in the septic HFD-fed mice in our study, has been shown to contribute to kidney injury in CLP-induced sepsis, as knockout of IL-17A improved functional and morphological measures of AKI, and exogenous administration of IL-17A aggravated AKI (45).…”
Section: Discussionsupporting
confidence: 90%
“…However, blockage of CXCR2 did not prevent neutrophil accumulation in liver sinusoids of obese animals. The receptor ligands in mice are CXCL1 (KC) and CXCL2 (MIP-2), known to regulate neutrophil chemotaxis [ 59 ], and their levels are also elevated in obesity [ 31 , 45 ]. CXCR2 works in tandem with CXCR1 and they share numerous ligands, however, some of them are unique to the former, including KC and MIP-2 [ 60 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is despite the fact that obese individuals are at greater risk of comorbidities such as diabetes, cardiovascular diseases, or liver abnormalities associated with shortened life expectancy [ 30 ]. However, not all studies confirm the very existence of such a paradox nor empirical studies minimizing bias and confounding factors were performed thus far [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although inflammation accompanying obesity appears as a low‐grade chronic inflammatory state, one can question whether the huge numbers of immune cells present in adipose tissue of patients with obesity might not represent a kind of time bomb contributing to the cytokine storm observed in COVID‐19. Despite perturbing data suggesting a paradoxical protection of obesity against bacterial sepsis (4), the opposite has been observed for influenza, pneumonia (4), and COVID‐19 (1).…”
Section: Obesity Involves An Inflammatory State Of Adipose Tissuementioning
confidence: 99%